Research Bulletin, June 2014. (IMF Research Bulletin; IMF Research Bulletin ;, 2014)
Articles in the June 2014 issue of the IMF Research Bulletin look at 'The Rise and Fall of Current Account Deficits in the Euro Area Periphery and the Baltics' (Joong Shik Kang and Jay C. Shambaugh) and 'The Two Sides of the Same Coin? Rebalancing and Inclusive Growth in China' (Il Houng Lee, Murtaza Syed, and Xin Wang). The Q and A looks at 'Seven Questions on the Monetary Transmission Mechanism in Low-Income Countries' (Andrew Berg, Luisa Charry, Rafael A. Portillo, and Jan Vleck). This issue of the Research Bulletin includes updated listings of IMF Working Papers, Staff Discussion Notes, and Recommended Readings from the IMF Bookstore. Readers can also find information on free access to a featured article from 'IMF Economic Review.'.